Analgesic Efficacy of Combined Adductor Canal and Popliteal Plexus Blocks Versus Adductor Canal Block Alone in Arthroscopic Knee Surgery: A Prospective, Double-Blinded, Randomized Trial - Ghada Magdy Behery; Nadia Hassan Fattoh; Mohammad Ali Mohammad Abduallah; Shimaa Elsaied Ibrahim Shaban (Bali Journal of Anesthesiology)
Background: The currently accepted standard for improving knee stability and function is anterior cruciate ligament reconstruction (ACLR). This study aimed to assess the postoperative analgesic efficacy of combining adductor canal (AC) and popliteal plexus blocks (PPB) to that obtained by using AC block (ACB) alone in arthroscopic ACLR. Materials and Methods: For elective arthroscopic ACLR, 110 male and female patients with American Society of Anesthesiologists physical status I or II, aged from 21 to 50 years, were randomly assigned to a double-blind, prospective trial. Patients were divided into two equal groups and given either ACB (15 mL of 0.25% bupivacaine) and PPB (15 mL of 0.25% bupivacaine) or ACB alone. Outcome parameters were 24-h morphine consumption, time-to-first rescue analgesia, and postoperative pain. Results: Group I used less morphine (6.45 ± 1.8 vs 11.22 ± 1.7 mg, P < 0.001) and required less time-to-first rescue analgesia (14.49 ± 2.27 vs. 13.64 ± 1.77 min, P = 0.030). At 12, 18, and 24 h, Group I had significantly lower postoperative pain scores (P = 0.007, 0.010, and 0.012, respectively) than Group II. Additionally, Group I also exhibited significantly less required time to be able to stand, walk, and exercise compared to Group II (P = 0.002, 0.013, and 0.035, respectively). Conclusion: ACB combined with PPB resulted in reduced morphine consumption, required less time-to-first rescue analgesia, exhibited lower postoperative pain scores, and required less time to rehabilitate compared to ACB alone.